INTERVENSI FISIOTERAPI PADA KASUS PASCA OPERASI RECONTRUCTION ANTERIOR CRUCIATE LIGAMENT DEXSTRA FASE 1: STUDY CASE - Oktavia Oktavia; Arin Supriyadi; Monalisa Monalisa (Journal of Innovation Research and Knowledge, 2023)
ACL reconstruction Is a surgical procedure by grafting the ACL using tendon tissue (Graft). This action is performed to restore stability to the knee and joint fixation. The condition after ACL reconstruction causes complications resulting in edema, pain, muscle weakness. The implementation of physiotherapy interventions in this case aims to determine the effect of Transcutaneous Electrical Nerve Stimulation (TENS), Range of Motion (ROM) exercise and Strengthening Exercise, in reducing pain, increasing range of motion and increase muscle strength in the knee joint. This research method was carried out directly to 1 respondent with an Anterior Cruciate Ligament (ACL) post-reconstruction condition. Phase 1 with therapy 3 times in 2 weeks. After doing the therapy 3 times in 2 weeks, the results showed a decrease in pain, a decrease in edema, an increase in the range of motion of the joints, and an increase in muscle strength. The conclusion obtained is that physiotherapy interventions in cases of post-anterior cruciate ligament reconstruction phase 1 are proven to be able to reduce pain, edema, increase range of motion of joints and increase muscle strength.